Phytohormone biosynthesis and transcriptional analyses provide insight into the main growth stage of male and female cones Pinus koraiensis - Li, Yan; Zhao, Minghui; Cai, Kewei; Liu, Lin; Han, Rui; Pei, Xiaona; Zhang, Lina; Zhao, Xiyang (Frontiers in Plant Science, 2023)
The cone is a crucial component of the whole life cycle of gymnosperm and an organ for sexual reproduction of gymnosperms. In Pinus koraiensis, the quantity and development process of male and female cones directly influence seed production, which in turn influences the tree's economic value. There are, however, due to the lack of genetic information and genomic data, the morphological development and molecular mechanism of female and male cones of P. koraiensis have not been analyzed. Long-term phenological observations were used in this study to document the main process of the growth of both male and female cones. Transcriptome sequencing and endogenous hormone levels at three critical developmental stages were then analyzed to identify the regulatory networks that control these stages of cones development. The most significant plant hormones influencing male and female cones growth were discovered to be gibberellin and brassinosteroids, according to measurements of endogenous hormone content. Additionally, transcriptome sequencing allowed the identification of 71,097 and 31,195 DEGs in male and female cones. The synthesis and control of plant hormones during cones growth were discovered via enrichment analysis of key enrichment pathways. FT and other flowering-related genes were discovered in the coexpression network of flower growth development, which contributed to the growth development of male and female cones of P. koraiensis. The findings of this work offer a cutting-edge foundation for understanding reproductive biology and the molecular mechanisms that control the growth development of male and female cones in P. koraiensis.